Beyond the tragedy in global fisheries - Webster, D. G., 1975- (Politics, science, and the environment., 2015)
An analysis of how responsive governance has shaped the evolution of global fisheries in cyclical patterns of depletion and rebuilding dubbed the "management treadmill."